Discovering the potential of Padang Besar, Perlis as a northern halal hub in Malaysia: A review - Md Rosdy, Afaf Syakirah; Jamaludin, Mohammad Aizat; Ahmad Fadzillah, Nurrulhidayah (Journal of Islamic, Social, Economics and Development, 2026)
The development of Muslim nations in terms of economic, political, and social stability has led to the emergence of the global halal hub. Malaysia has rapidly become the world's leading halal centre due to its pioneering role in the halal industry and certification, capitalising on its unique advantages to meet the increasing global demand for halal goods and services. Perlis, a state in Malaysia, has gained recognition from many stakeholders for its potential for economic growth. However, the potential of Padang Besar, Perlis, as a northern halal gateway remains underexplored in current academic literature. This article examines the feasibility of establishing a halal hub in northern Malaysia, with a particular focus on Padang Besar in Perlis. The study employed qualitative research methods through content analysis. Drawing on a range of scholarly works related to Malaysia’s halal industry, the research aims to identify opportunities or potential for positioning Perlis as a key player in Malaysia's halal market. The findings suggest that Padang Besar’s strategic geographical location, government support, and status as a tourist destination could enhance its potential as a halal hub. Nonetheless, to achieve this goal, all stakeholders must improve and develop the state's facilities, infrastructure, export capacity, economic regulations and policies, and enhance Perlis Halal Park, among other aspects, to attract investors and increase SME productivity. This study contributes to the existing literature on halal hubs in Malaysia.